2014
DOI: 10.7224/1537-2073.2013-023
|View full text |Cite
|
Sign up to set email alerts
|

A Pooled Analysis of Two Phase 3 Clinical Trials of Dalfampridine in Patients with Multiple Sclerosis

Abstract: Background:Two phase 3 clinical trials demonstrated that dalfampridine extended-release 10-mg tablets (D-ER), twice daily, significantly improved walking relative to placebo in patients with multiple sclerosis (MS). The objective of this study was to evaluate the efficacy and safety of D-ER in patients with MS using pooled data from the two phase 3 trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 30 publications
6
39
2
Order By: Relevance
“…Two phase III trials showed that oral administration of prolonged-release fampridine (PRfampridine; dalfampridine) increases walking speed in the timed 25-foot walk test (T25FW) in a subset of patients with MS (timed-walk responders) [6][7][8] . The active substance 4-aminopyridine (4-AP) leads to improved signal conduction in demyelinated axons via the blockade of voltage-gated potassium channels 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Two phase III trials showed that oral administration of prolonged-release fampridine (PRfampridine; dalfampridine) increases walking speed in the timed 25-foot walk test (T25FW) in a subset of patients with MS (timed-walk responders) [6][7][8] . The active substance 4-aminopyridine (4-AP) leads to improved signal conduction in demyelinated axons via the blockade of voltage-gated potassium channels 9 .…”
Section: Introductionmentioning
confidence: 99%
“…3 We showed that providing a progressive, multicomponent PT program customized to continuously challenge the individual's ability in balance, gait, strength, and coordination, concurrently with prescribed D-ER, helped this participant make adjustments to her gait pattern. Treadmill speed and duration of walking bouts were adjusted according to her individual ability and fatigue, but speed, endurance, and independence (reduced manual assistance and verbal cueing from the therapist and reduced reliance on handrails for reactive postural adjustments) were progressed in each session.…”
Section: Discussionmentioning
confidence: 88%
“…Manual assistance was provided as needed (eg, to facilitate increased step length); however, she was responsive to verbal cueing to four on-treatment visits compared with the maximum off-drug T25FW gait speed. 3 Responders average 25% improvement in T25FW gait speed, whereas the average change in nonresponders is only 7%. 3 Exercise and gait training interventions may be an excellent alternative or adjunct treatment for patients who do not respond meaningfully to D-ER alone.…”
Section: Interventionsmentioning
confidence: 91%
See 2 more Smart Citations